The online detection of halogenated hydrocarbon in the atmosphere. (July 2021) - Zhangcheng, Yuanzhe; Liu, Yuzhu; Zhang, Qihang; Chen, Yu; Saleem, Seher; Zhuo, Zeming; Li, Lei
Highlights: The on-line detection of halogenated hydrocarbons was realized under simulated experimental conditions. The combination of LIBS and SPAMS. The characteristic lines of halogen had been observed in the LIBS. The SPAMS observed the information of halogen isotope. The rotational isomers in halogenated hydrocarbon molecules were verified by experiments and theoretical calculations. Abstract: Halogenated hydrocarbons are one of the main causes of atmospheric environmental pollution. The online detection of atmospheric halogenated hydrocarbons is a valuable and challenging research area. In this work, Laser-induced breakdown spectroscopy (LIBS) was used for the direct detection of halogenated hydrocarbons in air and the characteristic lines of the related halogens can be observed by the obtained emission spectra. To solve the difficulty of LIBS in resolving halogen isotopes, the mass spectra of halogenated hydrocarbon aerosol samples were collected and analyzed by the self-developed single particle aerosol mass spectrometer (SPAMS). Finally, the Raman spectra of halogenated hydrocarbon samples were detected to supplement the molecular structure information. By comparing the theoretical calculation with the experimental results, two different conformations of halogenated hydrocarbon molecules were found in the obtained Raman spectrum. The combination of LIBS and SPAMS provides a new method for the online rapid detection of halogenated hydrocarbons in the atmosphere. The discovery of the halogenated hydrocarbon molecule in the Raman spectrum is also helpful to the further development of related detection work.